The Effect of Math Anxiety on Students' Numeration Literacy Ability - Hilman Mangkuwibawa; Dadan F Ramdhan; Muhammad Rifqi Mahmud; Choerunisa Rachmadani Siswanto; Edi Supriyadi (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2024)
This research is based on findings that students' low interest in mathematics subjects and the widespread assumption that mathematics is a difficult and scary subject, affecting students' numeracy. This is thought to be a result of students' math anxiety about. This study aims to describe students' mathematical anxiety and students' numeracy and describe the influence of both variables on grade V students of MIS Muhammadiyah Babakanloa. It investigated the relationship between math anxiety and numeracy among Class V students at MIS Muhammadiyah Babakanloa, involving 27 participants during the 2022/2023 academic year. The descriptive and inferential statistical analysis result shows that math anxiety negatively impacts confidence and accuracy in calculations, while objective numeracy acts as a partial mediator in the association between math anxiety and performance in numerical reasoning tasks, with no significant gender differences in numeracy observed. Students' negative perceptions of mathematics and the dull learning methods contribute to low interest and heightened anxiety in the subject, significantly impacting numeracy by 21.71%. The negative relationship suggests that increased math anxiety corresponds to decreased numeracy. These findings emphasize the importance for teachers to innovate and create engaging learning experiences to alleviate math anxiety and enhance numeracy among students.